FEMINISASI PERDAGANGAN MANUSIA (Masalah Perdagangan Manusia dalam Konteks Kekerasan terhadap Perempuan) - Willy Gaut (Institut Filsafat dan Teknologi Kreatif Ledalero, 2014)
It is not so easy to explain, let alone suggest solutions to the problem of human trafficking as a concrete challenge to basic human rights. As with other social problems that have multiple causes, so too does human trafficking have many causes. In this article the author intends to elucidate one important aspect in human trafficking, the susceptibility of women to become victims. By placing human trafficking within the context of violence towards women, the author intends to propose a response to the question regarding why women are so susceptible as victims. Kata-kata kunci: Perdagangan manusia, perempuan, diskriminasi, kekerasan, gender, dan seks.